Transcriptome characteristics during cell wall formation of endosperm cellularization and embryo differentiation in Arabidopsis - Li, Chengcheng; Hu, Fan; Chen, Hongyu; Zhao, Jie (Frontiers in Plant Science, 2022)
Embryonic and endosperm development are important biological events during Arabidopsis seed development, and are controlled by dynamic changes in a range of gene expression. Nevertheless, the regulatory mechanisms of endosperm cellularization and embryo differentiation remain unclear. Here, we characterized the early embryo and endosperm development of the naa15 mutant that had abnormal embryo differentiation and incomplete endosperm cellularization compared to WT of Arabidopsis, and comparatively investigated the changes of gene expressions in WT seeds at 3, 4, and 5 days after pollination (3W, 4W, and 5W) and the white homozygous aborted naa15 seeds at 5, 6, and 7 DAP (5M, 6M, and 7M) from naa15-1/+ siliques using RNA sequencing and qPCR assays. The transcriptome analyses showed that there were 2040 and 3630 differentially expressed genes (DEGs) in 4W (at endosperm cellularization initiation stage and heart embryo stage) vs 3W (at syncytium stage and globular embryo stage), and 5W (at end of endosperm cellularization stage and torpedo embryo stage) vs 4W, respectively. The KEGG and GO analyses showed that lipid metabolic processes and transmembrane transport related to cell wall biogenesis, cell division and differentiation, the plant hormone signaling pathway, photosynthesis, and transcription regulator activity were evidently enriched in WT and naa15. The heatmap and qPCR analyses showed that auxin response genes (ARFs), auxin transport genes (PINs) cytokinin synthesis genes (LOGs), cytokinin dehydrogenase genes (CKXs), cytokinin receptor, transcription factors (MYB, bHLH, MADS-box, and ERF) were significantly downregulated in naa15 compared to WT. A series of cell wall genes annotated to xyloglucan endotransglycosylase/hydrolase, pectin methyl esterase, and pectin methyl esterase inhibitor were also identified in these DEGs. Moreover, using an immunofluorescent assay, the features of cell walls displayed that cellulose fluorescence signals in the embryo and endosperm of naa15 were significantly decreased, and the signals of low- and high- methyl esterification of pectin were also obviously decreased in the endosperm of naa15. In summary, we identified a large number of DEGs and investigated the features of cell walls during endosperm cellularization and embryonic differentiation, which provided important information on transcription and gene expression to reveal their regulatory mechanisms.